Growth of Solutions to Higher Order Differential Equation with Meromorphic Coefficients (Communications in Mathematical Research, 2019)
In this paper, we study the growth of solutions of higher order differential equation with meromorphic coefficients, and find some conditions which guarantee that its every nontrivial solution is of infinite order.